Homonim dalam Bahasa Minangkabau di Nagari Tandikek: Kajian Semantik: Homonyms in the Minangkabau Language in the Nagari Tandikek: A Semantic Study - Pratami, Isra Rizka; Kusmana, Ade; Fitriah, Siti (Pena : Jurnal Pendidikan Bahasa dan Sastra, 2026)
This study aims to identify and analyze the semantic relationships of homonyms in the Minangkabau language as spoken in the village of Tandikek. The study employs a qualitative descriptive approach, focusing on the understanding of meaning, context, and language use among native speakers. Data were collected through observation and interviews, then analyzed using the distribution method and the equivalence method to determine word classes and meanings based on their contextual usage. The results indicate that there are ten homonymous words that share the same form but have distinct meanings and are not interrelated. These words are classified into four categories: noun–noun, noun–adjective, noun–verb, and verb. These findings suggest that homonymy does not occur solely within a single word class but can also involve shifts in grammatical function across word classes. Furthermore, this study confirms that context plays a crucial role in determining meaning, as identical word forms can potentially lead to ambiguity without the support of a clear speech situation. The novelty of this study lies in the use of linguistic data sourced directly from community speech in Nagari Tandikek, an area that has not been extensively studied. This study is expected to contribute to semantic research, particularly regarding semantic relations in regional languages, and to serve as a reference for the development of more contextually relevant language teaching materials.